Enhancing efficiency in photovoltaic hydrogen production: A comparative analysis of MPPT and electrolysis control strategies - Shen Yuong Wong; Jiawei Li (MethodsX, 2025)
With the rapid growth of photovoltaic installed capacity, photovoltaic hydrogen production can effectively solve the problem of electricity mismatch between new energy output and load demand. Photovoltaic electrolysis systems pose unique challenges due to their nonlinear, multivariable, and complex nature. This paper presents a thorough investigation into the control methodologies for such systems, focusing on both Maximum Power Point Tracking (MPPT) and electrolysis cell control strategies. Beginning with a comprehensive review of MPPT techniques, including classical, intelligent, optimization, and hybrid approaches, the study delves into the intricate dynamics of Proton Exchange Membrane Electrolysis Cells (PEMEL). Considering the nonlinear and time-varying characteristics of PEMEL, various control strategies such as Proportional-Integral-Derivative (PID), robust, Model Predictive Control (MPC), and Fault Tolerant Control (FTC) are analyzed. Evaluation metrics encompass stability, accuracy, computational complexity, and response speed. This paper provides a comparative analysis, encapsulating the strengths and limitations of each MPPT and PEM control technique.